2010
DOI: 10.1007/s10517-010-0910-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Combined Treatment with Resveratrol and Indole-3-Carbinol

Abstract: Male Wistar rats received a semisynthetic diet with resveratrol (100 mg/kg), indole-3-carbinol (20 mg/kg), or a mixture of these compounds in the same doses for 1 week. Activities of ethoxyresorufin dealkylase (EROD), methoxyresorufin dealkylase (MROD), pentoxyresorufin dealkylase (PROD), and 6β-testosterone hydroxylase (6β-TH) and the content of mRNA for CYP1A1, CYP1A2, and CYP3A1 were elevated in the liver of rats receiving indole-3-carbinol. These changes were accompanied by an increase in activity of phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Indole-3-carbinol was purchased from Sigma Chemical Co. (St. Louis, MO, USA). The dose used was selected according to previous studies 16 17 . Besides, pilot experimental trials of the present study were carried out for the same purpose.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indole-3-carbinol was purchased from Sigma Chemical Co. (St. Louis, MO, USA). The dose used was selected according to previous studies 16 17 . Besides, pilot experimental trials of the present study were carried out for the same purpose.…”
Section: Methodsmentioning
confidence: 99%
“…Indole-3-carbinol is a natural glucosinolate breakdown product found in cruciferous vegetables 15 . It was shown that indole-3-carbinol has the ability to increase the activity of some anti-oxidant enzymes such as hemoxygenase-1 and glutathione transferase 16 . Besides, several studies had confirmed the anti-inflammatory activities of indole-3-carbinol in a variety of animal models such as aspirin-induced gastric ulcer 17 , liver fibrosis 18 , lipopolysaccharide-induced acute lung injury 19 and high fat diet-induced obesity 20 .…”
mentioning
confidence: 99%